Homologous Recombination in Protozoan Parasites and Recombinase Inhibitors - Andrew A. Kelso; Andrew A. Kelso; Sarah M. Waldvogel; Adam J. Luthman; Michael G. Sehorn; Michael G. Sehorn; Michael G. Sehorn; Michael G. Sehorn (Frontiers in Microbiology, 2017)
Homologous recombination (HR) is a DNA double-strand break (DSB) repair pathway that utilizes a homologous template to fully repair the damaged DNA. HR is critical to maintain genome stability and to ensure genetic diversity during meiosis. A specialized class of enzymes known as recombinases facilitate the exchange of genetic information between sister chromatids or homologous chromosomes with the help of numerous protein accessory factors. The majority of the HR machinery is highly conserved among eukaryotes. In many protozoan parasites, HR is an essential DSB repair pathway that allows these organisms to adapt to environmental conditions and evade host immune systems through genetic recombination. Therefore, small molecule inhibitors, capable of disrupting HR in protozoan parasites, represent potential therapeutic options. A number of small molecule inhibitors were identified that disrupt the activities of the human recombinase RAD51. Recent studies have examined the effect of two of these molecules on the Entamoeba recombinases. Here, we discuss the current understandings of HR in the protozoan parasites Trypanosoma, Leishmania, Plasmodium, and Entamoeba, and we review the small molecule inhibitors known to disrupt human RAD51 activity.